Poor outcome after systemic therapy in secondary high-grade pancreatic neuroendocrine tumors - Kazhan Mollazadegan; Britt Skogseid; Johan Botling; Tobias Åkerström; Barbro Eriksson; Staffan Welin; Anders Sundin; Joakim Crona (Endocrine Connections, 2022)
Longitudinal changes in pancreatic neuroendocrine tumor (panNET) cell proliferation correlate with fast disease progression and poor prognosis. The optimal treatment strategy for secondary panNET grade (G)3 that has progressed from a previous low-or intermediate-grade to high-grade panNET G3 is currently unknown. This was a single-center retrospective cohort study aimed to characterize treatment patterns and outcomes among patients with secondary panNET-G3. Radiological responses were assessed using the Response Evaluation Criteria in Solid Tumors version 1.1. A total of 22 patients were included and received a median of 2 (range, 1–4) treatment lines in 14 different combinations. Median overall survival (OS) was 9 month s (interquartile range (IQR): 4.25–17.5). For the 15 patients who received platinum–etoposide chemotherapy, median OS was 7.5 months (IQR: 3.75–10) and median progression- free survival (PFS) was 4 months (IQR: 2.5–5.5). The 15 patients who received conventional panNET therapies achieved a median OS of 8 months (IQR: 5–16.75) and median PFS was 5.5 months (IQR: 2.75–8.25). We observed one partial response on 177Lu DOTA-TATE therapy. In conclusion, this hypothesis-generating study failed to identify any promising treatment alternatives for patients with secondary panNET-G3. This demonstrates the ne ed for both improved biological understanding of this particular NET entity and for designing prospective studies to further assess its treatment in larger patient cohorts.